Implication of Extracellular Signal-Regulated Kinase in the Expression of Natural Reward: Evidence Not Found - Amaral, Inês M.; Hofer, Alex; El Rawas, Rana (Frontiers in Behavioral Neuroscience, 2022)
Many studies have implicated extracellular signal-regulated kinase (ERK) in drug-rewarding properties. Yet, only few investigated if ERK also mediates the naturally rewarding stimuli. In this study, we compared ERK activation in the nucleus accumbens (NAc) after cocaine reward and after positive social interaction with a partner-reward in male rats. With our protocol, ERK phosphorylation in the NAc was not increased after cocaine reward. In addition, the interaction with a social partner did not alter ERK activation in the NAc. These results suggest that ERK in the NAc may not be involved in natural reward learning. Social interaction (SI) in an alternative context to the one associated to drugs of abuse can abolish drug preference. Given that intra-NAc core-ERK inhibition impaired the expression of cocaine preference, we wanted to investigate if the protective effects of SI when an individual is allowed to interact with a social partner in an alternative context to the one associated to drugs during the learning phase are enhanced by ERK inhibition. For that, U0126 was bilaterally infused into the NAc core of rats conditioned with cocaine in one context and with social interaction in the opposite context before assessing the expression of reward-related learning. Intra-NAc core ERK inhibition was ineffective to impair the expression of drug reward as previously demonstrated, when a social partner was available in an alternative context. Thus, the effects of the pharmacological manipulations based on decreasing ERK activity are not cumulative to other treatments for drug addiction based on social interaction.